Psychometric properties of the Centers for Disease Control and Prevention Health-Related Quality of Life (CDC HRQOL) items in adults with arthritis - Mielenz, Thelma (BioMed Central, 2006)
BACKGROUND: Measuring health-related quality of life (HRQOL) is important in arthritis and the SF-36v2 is the current state-of-the-art. It is only emerging how well the Centers for Disease Control and Prevention (CDC) HRQOL measures HRQOL for people with arthritis. This study's purpose is to assess the psychometric properties of the 9-item CDC HRQOL (4-item Healthy Days Core Module and 5-item Healthy Days Symptoms Module) in an arthritis sample using the SF-36v2 as a comparison. METHODS: In Fall 2002, a cross-sectional study acquired survey data including the CDC HRQOL and SF-36v2 from 2 North Carolina populations of adult patients reporting osteoarthritis, rheumatoid arthritis, and fibromyalgia; 2182 (52%) responded. The first item of both the CDC HRQOL and the SF-36v2 was general health (GEN). All 8 other CDC HRQOL items ask for the number of days in the past 30 days that respondents experienced various aspects of HRQOL. Exploratory principal components analyses (PCA) were conducted on each sample and the combined samples of the CDC HRQOL. The multitrait-multimethod matrix (MTMM) was used to compute correlations between each trait (physical health and mental health) and between each method of measurement (CDC HRQOL and SF36v2). The relative contribution of the CDC HRQOL in predicting the physical component summary (PCS) and the mental component summary (MCS) was determined by regressing the CDC HRQOL items on the PCS and MCS scales. RESULTS: All 9 CDC HRQOL items loaded primarily onto 1 factor (explaining 57% of the item variance) representing a reasonable solution for capturing overall HRQOL. After rotation a 2 factor interpretation for the 9 items was clear, with 4 items capturing physical health (physical, activity, pain, and energy days) and 3 items capturing mental health (mental, depression, and anxiety days). All of the loadings for these two factors were greater than 0.70. The CDC HRQOL physical health factor correlated with PCS (r = -.78, p < 0.0001) and the mental health factor correlated with MCS (r = -.71, p < 0.0001). The relative contribution of the CDC HRQOL in predicting PCS was 73% (R(2 )= .73) when GEN was included in the CDC HRQOL score and 65% (R(2 )= .65) when GEN was removed. The relative contribution of the CDC HRQOL in predicting MCS was 56% (R(2 )= .56) when GEN was included and removed. CONCLUSION: The CDC HRQOL appears to have strong psychometric properties in individuals with arthritis in both community-based and subspecialty clinical settings. The 9 item CDC HRQOL is a reasonable measure for overall HRQOL and the two subscales, representing physical and mental health, are reasonable when the goal is to examine those aspects.